The Impact of Coronavirus Disease 2019 Pandemic on Female Patients Seeking or Undergoing Fertility Treatment in a Single In Vitro Fertilisation Clinic in Greece: An International, Cross-Sectional Study - Konstantina Pappa; Emmanouil M. Xydias; Apostolos C. Ziogas; Kanelina Bimba; Elias Tsakos; Efstratios Kolibianakis (Journal of Human Reproductive Sciences)
Background: The temporary delay in fertility treatments due to the coronavirus disease 2019 (COVID-19) pandemic, in combination with the imposed lockdowns, has created psychological distress and anxiety amongst infertile patients. Aims: The aim of this study was to evaluate how the pandemic has influenced assisted reproduction technology (ART) patients in Greece, during the second wave of the pandemic. An additional aim was to examine the effects of the pandemic on cross-border patients in particular, compared to national ones. Settings and Design: This study was a cross-sectional, questionnaire-based study, distributed to 409 patients of a single in vitro fertilisation (IVF) clinic in Greece, during the period between January until the end of April 2021. Materials and Methods: The survey was conducted online via E-mail and was distributed to national and international female patients of a single IVF clinic in Greece, who were undergoing ART treatment during the second wave of the COVID-19 pandemic. Patient participation was anonymous, and participants provided informed consent for collection and publication of data. Statistical Analysis Used: The mean values of baseline characteristics, along with answer percentages per questionnaire item, were calculated. Collected data were cross-tabulated, and the Chi-square test was used as a measurement of the differences between national and cross-border patients. A P value lower than 0.05 was considered statistically significant. All analyses were conducted using the SPSS Statistics software. Results: From 409 initial candidates, 106 women, with a mean age of 41.2 years, completed the questionnaire (26% response rate). The majority of national patients did not experience any delays in their fertility plans (62%), while cross-border patients experienced over 6 months of delays (54.7%). The main reason for fertility postponement was travel restrictions due to COVID-19 for cross-border patients (62.5%), while national patients cited additional reasons. The majority of patients experienced a degree of stress (65.2%) due to the delays, however were not fearful of COVID-19 infection (54.7%). Most patients were aware of the protective measures taken by IVF clinics (80.2%), and this was a determinant factor (71.7%) for their decision to restart their fertility treatment. Conclusion: The COVID-19 pandemic lockdowns had a significant emotional impact on patient receiving or undergoing ART treatment in Greece. This impact was more pronounced on cross-border patients. This highlights the need for continuation of ART care, with the appropriate protective measures, during the pandemic, as well as during similar times of crisis in the future.